INFLUENCE OF DIFFERENT COLOR SHADING SCREENS ON AMERICAN LETTUCE DEVELOPMENT - Rech, L. L.; Lopes, A. R.; Dotto, M.; Giarola, C. M.; Pirola, K. (Revista Brasileira de Engenharia de Biossistemas, 2019)
The use of color shading screens aims at better protect against solar radiation. This study aimed to evaluate the influence of different colors on shading screens on the development of american lettuce. The experiment was conducted in São João, Paraná. The experimental design was randomized complete block design (DBC) with 6 groups and 4 replications: T1: Open field cultivation, T2: Blue shading Screen, T3: Silver shading screen, T4: Black shading screen, T5: Green shading screen and T6: Red shading screen. Lettuce development was evaluated for root weight, root length, head diameter, leaf number, fresh mass and head weight. Lettuce without shading screen presented the best development, among the studied shading screens the red schading screen had a negative highlight, Always with the worst agronomic performance.